Activating Background Knowledge: An Effective Strategy to Develop Reading Comprehension Skills - Shubhada Kedar Deshpande (Journal of English Language Teaching and Linguistics, 2016)
The present paper is a report on a small classroom based research study. The researcher has tried Activating Background Knowledge as a strategy to improve reading comprehension skills of the students in the First Year B.Com. Classroom in a degree college affiliated to the University of Mumbai. The teacher-researcher assigned two passages dealing with two different social issues and set in two different contexts, i.e., foreign and local, for comprehension to the students in the classroom. The classroom experience indicated that activating and building on the students’ background knowledge did help in facilitating their reading comprehension skills. The paper thus recommends it as an effective strategy to develop the students’ reading comprehension skills.